Method of forming recommendations using temporal constraints in a situation of cyclic cold start of the recommender system - Chalyi, S.; Leshchynskyi, V.; Leshchynska, I. (My University, 2020)
The problem of the formation of the recommended list of items in the situation of cyclic cold start of the recommendation system is considered. This problem occurs when building recommendations for occasional users. The interests of such consumers change significantly over time. These users are considered “cold” when accessing the recommendation system. A method for building recommendations in a cyclical cold start situation using temporal constraints is proposed. Temporal constraints are formed on the basis of the selection of repetitive pairs of actions for choosing the same objects at a given level of time granulation. Input data is represented by a set of user choice records. For each entry, a time stamp is indicated. The method includes the phases of the formation of temporal constraints, the addition of source data using these constraints, as well as the formation of recommendations using the collaborative filtering algorithm. The proposed method makes it possible, with the help of temporal constraints, to improve the accuracy of recommendations for “cold” users with periodic changes in their interests. Розглянуто проблему формування рекомендованого переліку пунктів у ситуації циклічного холодного початку системи рекомендацій. Ця проблема виникає при складанні рекомендацій для випадкових користувачів. Інтереси таких споживачів з часом значно змінюються. Ці користувачі вважаються "холодними" під час доступу до системи рекомендацій. Запропоновано метод побудови рекомендацій у циклічній ситуації з холодним початком із застосуванням тимчасових обмежень. Тимчасові обмеження формуються на основі вибору повторюваних пар дій для вибору одних і тих же об'єктів на заданому рівні гранулювання часу. Вхідні дані представлені набором записів про вибір користувача. Для кожного запису вказується штамп часу. Метод включає фази формування тимчасових обмежень, додавання вихідних даних з використанням цих обмежень, а також формування рекомендацій з використанням алгоритму спільної фільтрації. Запропонований метод дає змогу за допомогою тимчасових обмежень підвищити точність рекомендацій для "холодних" користувачів з періодичними змінами їх інтересів.
Keywords: recommendation system; temporal constraints; personalization of recommendations; area under the curve